Informe de viaje a Cajamarca (9-14/10/89), incluyendo un analisis preliminar de algunos datos obtenidos en el sondeo sobre semilla - Maître, Adrian (International Center for Tropical Agriculture, 1989)
Seed survey data gathered by the bean project for the Andean region during the 1989/90 cropping season are presented. Five aspects were considered: the farmer`s concept of seed, the farmer`s opinion on quality and availability, and the technical feasibility of production and distribution-commercialization. The farmer considers seed as an important input that allows him to continue his work and sometimes provides him with different var. New seed is not purchased to improve quality but to solve the problem of availability or when a farmer wants to multiply a new var. The role that small-scale seed production should play in the distribution, vol. and area planted to several var. is indicated. Several alternatives are also given. (CIAT)